Glycoform-resolved FcɣRIIIa affinity chromatography–mass spectrometry. Issue 7 (3rd October 2019) - Lippold, Steffen; Nicolardi, Simone; Domínguez-Vega, Elena; Heidenreich, Anna-Katharina; Vidarsson, Gestur; Reusch, Dietmar; Haberger, Markus; Wuhrer, Manfred; Falck, David
ABSTRACT: Determination of the impact of individual antibody glycoforms on FcɣRIIIa affinity, and consequently antibody-dependent cell-mediated cytotoxicity (ADCC) previously required high purity glycoengineering. We hyphenated FcɣRIIIa affinity chromatography to mass spectrometry, which allowed direct affinity comparison of glycoforms of intact monoclonal antibodies. The approach enabled reproduction and refinement of known glycosylation effects, and insights on afucosylation pairing as well as on low-abundant, unstudied glycoforms. Our method greatly improves the understanding of individual glycoform structure–function relationships. Thus, it is highly relevant for assessing Fc-glycosylation critical quality attributes related to ADCC.